DEM modelling of breakage behaviour of semi-brittle agglomerates subject to compaction and impaction - Li, L.J.; Zhu, Q.X.; Gou, D.Z.; Chan, H.-K.; Kourmatzis, A.; Zhao, G.T.; Yang, R.Y. (Powder technology, 2022)
Drug powder in API-only dry powder inhalers (DPIs) is prepared in a form of agglomerates for easy handling and transport. Agglomerates tend to recrystallize due to temperature variation or being stored in a high humidity environment, causing the formation of solid bonds between particles which makes the agglomerates more difficult to disperse. This paper conducted a numerical study of breakage of hard, semi-brittle agglomerates using the discrete element method (DEM). A solid bonding model was adopted to mimic the brittle behaviour of the agglomerates and the coarse grain (CG) approach was applied to reduce the number of particles in the simulations. The simulated agglomerates showed the breakage behaviour upon impaction with a wall comparable to the experimental observation. The agglomerates with reasonable CG scaling ratios had similar structural properties and mechanical strengths upon compaction. Upon impaction with a wall at different velocities and angles, the agglomerate breakage was dominated by the normal impact energy with impact angle approaching to 90-degree causing more damage to the agglomerates. Such behaviour was different from that of soft agglomerates held by the van der Waals force in which both normal and shear forces played important roles in agglomerate breakage. [Display omitted] •The breakage of semi-brittle agglomerates subject to compaction and impaction was modelled by DEM.•Solid bonding force was adopted to mimic the brittle behaviour of agglomerates.•The simulations were comparable to experimental observation.•The distinctive semi-brittle breakage pattern of the agglomerates was different from that of the soft agglomerates.•The normal impact energy dominated the breakage of hard agglomerates.